Dispute Resolution on Overlapping Land Certificate Through Mediation Based on The Regulation of The Minister of Agrarian Affairs And Spatial Planning Number 11 Year 2016 - Sabda Ghaly Al Banna; Diana Fitriana (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
This study has the purpose of examining and analyzing mediation efforts in resolving land ownership disputes at the Bekasi City Land Office. In addition, it also analyzes the legal protection for parties to land disputes based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning Number 11 of 2016. The research method used is normative juridical research method. The normative juridical research method is a legal analysis based on legal norms, principles, and doctrines. The results showed that the application of mediation in land ownership disputes at the Bekasi City Land Office has not been effective enough. In 2017-2020, the Bekasi City Land Office was only able to resolve disputes through mediation with a limited number of cases. This is due to external and internal obstacles experienced by the section for controlling and handling land disputes. In addition, legal protection in resolving land disputes at the Bekasi City Land Office is actually not enough to provide legal protection, because the results of the mediation carried out are still not optimal. Internal and external obstacles experienced, causing repressive legal protection has not been fulfilled for the parties to the dispute.